Impact of percutaneous coronary intervention with different guidance modalities in patients with coronary artery lesions: a network meta-analysis and systematic review - Jiang, Tao; Huang, Jie; Luo, Lisha; Li, Miaoling; Chen, Gong (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTraditional coronary angiography has inherent limitations in terms of lesion assessment and stenting. New guidance modalities to guide percutaneous coronary intervention (PCI) are now available.MethodsWe systematically searched PubMed, Embase, Cochrane, and Web of Science databases for the period from the time of construction to 25 April 2024. A network meta-analysis of randomized controlled trials (RCT) was performed to determine the optimal treatment strategy by comparing the short-term outcome and long-term prognosis of adverse cardiovascular outcomes in patients with coronary artery lesions after eight different PCI-guided modalities. The clinical outcomes included major adverse cardiovascular events (MACE), all-cause mortality, cardiac death, myocardial infarction, and target vessel revascularization (TVR). Risk ratios (RR) with 95% confidence intervals (CI) were calculated.ResultsForty randomized controlled trials with a total of 38,107 patients were included. In the MACE subgroup up to 12 months, Intravascular Ultrasound-guided Percutaneous Coronary Intervention (IVUS-PCI) [RR = 1.60, 95%CI = (1.10, 2.30)], Optical Frequency Domain Imaging-guided Percutaneous Coronary Intervention (OFDI-PCI) [RR = 2.36, 95%CI = (1.05, 5.80)] and Quantitative Flow Ratio-guided Percutaneous Coronary Intervention (QFR-PCI) [RR = 1.45, 95%CI = (1.15, 1.83)] significantly reduced the incidence of MACE. In the MACE subgroup at 12 months, Fractional Flow Reserve-guided Percutaneous Coronary Intervention (FFR-PCI) [RR = 0.72, 95%CI = (0.49, 0.99)], IVUS-PCI [RR = 0.66, 95%CI = (0.43, 0.99)] and Optical Coherence Tomography-guided Percutaneous Coronary Intervention [RR = 0.59, 95%CI = (0.35, 0.92)] all significantly reduced the incidence of MACE in patients. FFR-PCI [RR = 0.42, 95%CI = (0.20, 0.75)] significantly reduced the incidence of cardiac death in patients compared to Angiography-guided Percutaneous Coronary Intervention (Angio-PCI). FFR-PCI [RR = 0.78, 95%CI = (0.62, 0.99)], OCT-PCI [RR = 0.59, 95%CI = (0.35, 0.97)], QFR-PCI [RR = 0.64, 95%CI = (0.45, 0.91)] were associated with a lower risk of myocardial infarction compared to Angio-PCI. The incidence of Target Vessel Revascularization (TVR) was significantly lower in patients who underwent IVUS-PCI [RR = 0.57, 95%CI = (0.36, 0.86)], OCT-PCI [RR = 0.47, 95%CI = (0.24, 0.95)] than in those who underwent Angio-PCI. However, there were no significant differences between the different guidance modalities and subgroup analyses in improving overall survival.ConclusionIVUS and OCT were more effective in reducing MACE and TVR. This suggests that IVUS and OCT may be the best strategies in the interventional management of complex coronary lesions.Systematic Review RegistrationPROSPERO CRD42024567598.